2016
DOI: 10.1186/s12904-016-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for transferral to emergency departments of terminally ill patients - a French descriptive and retrospective study

Abstract: BackgroundPatients under palliative care and in hospital-at-home services are frequently transferred to emergency departments.We set out to identify the reasons for these presentations to determine the proportion that might be avoidable.MethodsWe conducted a retrospective study by assessment of patient files.We studied admissions to four emergency departments in an area of France (Puy-de-Dôme) between September 2011 and August 2013. Reasons for transfer and diagnostic conclusion by emergency doctors were noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Indeed, although the benefits associated with hospitalization for patients with palliative care needs cannot be denied [ 5 ], ED visits are considered an indicator of poor quality in home care services [ 6 ]. Moreover, several studies have shown that ED visits in IHPC patients are not essential and potentially avoidable [ 7 10 ]. The Italian healthcare system has initiated a shift from institutional palliative care to IHPC, and many efforts have been made to improve the access to and quality of IHPC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although the benefits associated with hospitalization for patients with palliative care needs cannot be denied [ 5 ], ED visits are considered an indicator of poor quality in home care services [ 6 ]. Moreover, several studies have shown that ED visits in IHPC patients are not essential and potentially avoidable [ 7 10 ]. The Italian healthcare system has initiated a shift from institutional palliative care to IHPC, and many efforts have been made to improve the access to and quality of IHPC.…”
Section: Introductionmentioning
confidence: 99%
“…36 Our results showed that, as the distance between the patient's home and the closest ED increases, the risk of ED visits decreases. Coherently with previous studies in France, 37 Sweden, 38 and the United Kingdom, 39 a reduced travel distance can increase the likelihood ED visits, independently of the severity of the medical condition 40,41 thus increasing health costs despite the effective need.…”
Section: Discussionmentioning
confidence: 63%
“…Previously, Cornillon et al [ 11 ] investigated the emergency transfers of terminally ill patients in France and suggested that only of 52 emergency department visits, 23 (44.2%) contacted HCPs before calling for emergency transfers and that 66% of the cases were admitted or DOA. Although our findings cannot be directly compared with those of the previous study due to the difference of study settings, judgments calling for EMS transfers were generally justified in our study.…”
Section: Discussionmentioning
confidence: 99%